(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
The present research is developed within the need to contribute to society with tools for the media literacy of individuals and their relationship with the arts, as an answer to the new educational and technological paradigm that is taking place in Spain. We will analyze the results of an educational methodology of the media skills through video), developed in non-formal education for students of high intellectual capacities of 3rd ESO, based on comparative research.